Upaya Pemerintah dalam Penyelesaian Konflik dengan Kelompok Kriminal Bersenjata (KKB) di Papua (Studi Komparasi dengan Kelompok Gerakan Aceh Merdeka (GAM) di Aceh) - Jhon Paris Pasaribu; Dian Ekawaty Ismail; Mellisa Towadi (Universitas Sains dan Teknologi Komputer, 2023)
The conflict between the Indonesian government and the KKB separatist group in Papua is a conflict that has existed for a long time and until now there has been no meeting point. The Indonesian government has taken various ways to resolve the conflict. Previously, Indonesia had also been faced with the same problem. Namely the Free Aceh Movement (GAM) group which demanded that Aceh be independent and stand alone as a legitimate state. In both conflicts, it has caused unconduciveness in society, both in terms of economy, politics, and so on. As a result of both conflicts, both with KKB and GAM have claimed many lives and have even targeted civilians. Then in an effort to resolve the government has a different way. In this study, the author will describe how the government's efforts to resolve conflicts with the Armed Criminal Group (KKB) in Papua and also with the Free Aceh Movement (GAM) group in Aceh differ.